Enhance the Terahertz Wave by Varying the Laser Beam Intensity via Relativistic Plasma - Bashair A. Abdul Khudher (Journal of Global Pharma Technology, 2019)
In this work, the use of 14CO2">  laser and high intensity at the wavelength 10.6 14Î¼m">  with Gaussian beam shape. This research focuses on the derivation of the equation which represents interaction between laser and plasma parameters in to states paraxial and nonparaxial in the case of self-focusing .The interaction of the laser with longitudinal magneto plasma occurs. The relation between the laser beam width and normalized distance parameters for three types intensities (0.9, 0.8, 0.7) self-focusing were studied. Then the best result self-focusing obtained at high intensity and at the lowest intensity, the self-focusing become weak .In nonparaxial beam the self-focusing been very weak and the best state at in high intensity and then at least intensity there no self-focusing exist .The THz radiation in case of paraxial beam is appear clearly with clean peaks (high resolution) so that the best at the power full self-focusing, either case nonparaxial beam obtained on the semi-stability phenomena. These results were studied and discussion.Keywords: Relativistic nonlinearity, Magneto plasma, Non paraxial, Terahertz radiation, Laser density, Self-focusing.